Prevalence and Consistency in Surgical Outcome Reporting for Femoroacetabular Impingement Syndrome: A Scoping Review - Reiman, Michael P.; Peters, Scott; Sylvain, Jonathan; Hagymasi, Seth; Ayeni, Olufemi R. (Arthroscopy, 2018)
The purposes of this review were (1) to collate and synthesize research studies reporting any outcome measure on both open and arthroscopic surgical treatment of femoroacetabular impingement (FAI) syndrome and (2) to report the prevalence and consistency of outcomes across the included studies. A computer-assisted literature search of the MEDLINE, CINAHL (Cumulative Index to Nursing and Allied Health Literature), and Embase databases was conducted using keywords related to FAI syndrome and both open and arthroscopic surgical outcomes, resulting in 2,614 studies, with 163 studies involving 14,824 subjects meeting the inclusion criteria. Two authors independently reviewed study inclusion and data extraction with independent verification. The prevalence of reported outcomes was calculated and verified by separate authors. Between 2004 and 2016, there has been a 2,600% increase in the publication of surgical outcome studies. Patients had a mean duration of symptoms of 27.7 ± 21.5 months before surgery. Arthroscopy was the surgical treatment used in 71% of studies. The mean final follow-up period after surgery was 32.2 ± 17.3 months. Follow-up time frames were reported in 78% of studies. Ten different patient-reported outcome measures were reported. The alpha angle was reported to be measured 42% less frequently as a surgical outcome than as a surgical indication. Surgical complications were addressed in only 53% of studies and failures in 69%. Labral pathology (91% of studies reporting) and chondral pathology (61%) were the primary coexisting pathologies reported. Clinical signs, as defined by the Warwick Agreement on FAI syndrome, were reported in fewer than 25% of studies. Most FAI syndrome patients have longstanding pain and potential coexisting pathology. Patient-reported outcome measures and diagnostic imaging are the most frequently reported outcomes. Measures of hip strength and range of motion are under-reported. It is unclear whether the inconsistency in reporting is because of lack of measurement or lack of reporting of specific outcomes in these studies. Current surgical outcomes are limited to mid-term surgical follow-up time frames and inconsistent outcome reporting. Level IV, systematic review of Level I through IV studies.